2004
DOI: 10.1111/j.1523-1755.2004.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of costimulatory molecules CD80/CD86 expression in IgA nephropathy

Abstract: This study suggested that CD80 and CD86 activate T cells in IgAN, CD80/CD86 expressions correlated with renal function at the time of renal biopsy, and monocyte/macrophages and tubular epithelial cells act as APC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…These cells highly expressed CD73, CD90, and CD105, but lacked expression of CD14, CD34, and CD45 (Figure 3), indicating the absence of contaminating hematopoietic cells in the culture [22]. In accordance with previous reports, these cells also demonstrated a lack of the co-stimulatory molecules CD80 and CD86 [23], conferring the ability to escape from immune surveillance. The immunophenotypic characteristics of the cultured cells satisfied the criteria for MSC surface markers as defined by the International Society for Cellular Therapy [24].…”
Section: Discussionsupporting
confidence: 83%
“…These cells highly expressed CD73, CD90, and CD105, but lacked expression of CD14, CD34, and CD45 (Figure 3), indicating the absence of contaminating hematopoietic cells in the culture [22]. In accordance with previous reports, these cells also demonstrated a lack of the co-stimulatory molecules CD80 and CD86 [23], conferring the ability to escape from immune surveillance. The immunophenotypic characteristics of the cultured cells satisfied the criteria for MSC surface markers as defined by the International Society for Cellular Therapy [24].…”
Section: Discussionsupporting
confidence: 83%
“…In IgAN, CD86 is predominantly expressed in the glomeruli and in the peritubular interstitium and CD80/CD86 expression levels correlate with renal function at the time of renal biopsy. Most CD86 + cells are monocytes and macrophages [20]. …”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have shown that renal biopsy of MpIgAN patients revealed increased interstitial cellular infiltration and tubular atrophy compared with SpIgAN patients. We found increased chemotaxis of CD45ϩ cells, CD3ϩ, CD4ϩ, CD8ϩ, CD20ϩ lymphocytes, and CD25ϩ monocytes in culture experiments in which tubular epithelial cells were stimulated with the IgA-HMC medium (21,22,44). In our in vitro culture setting, PBMC were chemoattracted to PTEC, which were exposed to the IgA-HMC medium on the apical surface.…”
Section: Discussionmentioning
confidence: 87%